Efficient Bargaining and the Skill-Structure of Wages and Employment - Ulrich Kaiser; Winfried Pohlmeier (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
This paper presents structural estimates for a bargaining model which nests the right-to-manage, the efficient wage bargaining, the seniority and the standard neo- classical labor demand model as special cases. In contrast to most existing models, our approach accounts for heterogeneous skill groups which differ in terms of productivity and representation in the bargaining process through union preferences. The paper in- troduces the concept of `virtual' firms which allows us to (i) test the eÆcient contract model against models implying that firms operate on the labor demand curve and to (i) overcome a potential misspecification of firms' output markets. Estimates of structural parameters are obtained from a novel crosssection of German firms of the business related service sector which includes information on skill-specific wage rates at the firm level. Central results of this paper are that unions do care about both wages and employment in the bargaining process and that firms operate on the contract curve. The bargaining power of unions in East Germany turns out to be much weaker than in West Germany.
urn:nbn:de:bsz:352-opus-5566
Keywords: L8; C22; C25; G10; 330; Lohnverhandlungstheorie; Qualifikation; Lohnstruktur; Arbeitsnachfrage; Humankapital; Arbeitsvertrag; Vertragstheorie; Theorie; Schätzung; Unternehmensdienstleistung; Deutschland